Lattice codes for the Gaussian wiretap channel - Belfiore, Jean-Claude (2011)
It has been shown recently that coding for the Gaussian Wiretap Channel can be done with nested lattices. A fine lattice intended to the legitimate user must be designed as a usual lattice code for the Gaussian Channel, while a coarse lattice is added to introduce confusion at the eavesdroppper, whose theta series must be minimized. We study, here, the behavior of this invariant for a class of lattices.